2021
DOI: 10.3389/fphys.2021.668236
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction-Related Gene Expression in the Antennae of Female Mosquitoes From Common Aedes aegypti Laboratory Strains

Abstract: Adult female mosquitoes rely on olfactory cues like carbon dioxide and other small molecules to find vertebrate hosts to acquire blood. The molecular physiology of the mosquito olfactory system is critical for their host preferences. Many laboratory strains of the yellow fever mosquito Aedes aegypti have been established since the late 19th century. These strains have been used for most molecular studies in this species. Some earlier comparative studies have identified significant physiological differences bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 74 publications
(134 reference statements)
0
9
0
Order By: Relevance
“…Interestingly, another study found differences in antennal olfactory gene expression across strains of Ae. aegypti , including members of the IR75 subfamily (Mitra et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, another study found differences in antennal olfactory gene expression across strains of Ae. aegypti , including members of the IR75 subfamily (Mitra et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, another study found differences in antennal olfactory gene expression across strains of Ae. aegypti , including members of the IR75 subfamily (Mitra et al 2021). While the evidence is circumstantial, results like these may hint at differences in CA responses in adult females, depending on natural variations in populations or physiological states.…”
Section: Discussionmentioning
confidence: 99%
“…Primers for nkaβ2 (Gene ID: 5573862) and ribosomal protein s7 ( rps7 ) were designed using PrimerBLAST [ 39 ] and NetPrimer (Premier Biosoft, Palo Alto, CA, USA) as previously described [ 40 ] (see Table 1 for primer sequences).…”
Section: Methodsmentioning
confidence: 99%
“…Primers were designed to flank intron sequences to discriminate between mRNA and genomic DNA amplification products. Primers for the vitellogenin ( vg ), beta-actin ( β-actin ) and ribosomal protein S7 ( rps7 ) genes have been published previously [ 45 , 46 ] (see Table 3 for all primer sequences). All qRT-PCR primers were synthesized at the 10-nmol scale with standard desalting purification (Eurofins Genomics, Louisville, KY, USA).…”
Section: Methodsmentioning
confidence: 99%